Agregação de ume nitossolo vermelho distroférrico sob sistemas de plantio direto, preparo convencional e mata nativa - de Assis, Renato L.; Lanças, Kleber Pereira [UNESP] (Soc Brasil Engenharia Agricola, 2010)
This study aimed to evaluate the effect of time since the adoption of the no-till system, in comparison with a native forest area and a conventional tillage area, using the distribution of soil aggregates in a Distroferric Red Nitosol. Treatments were as follows: native forest (NF), conventional tillage (CT), no-till for one year (NT1), no-till for four years (NT4), no-till for five years (NT5), and no-till for 12 years (NT12). Aggregate samples were collected randomly within each treatment at depths of 0-5 and 10-15 cm. After sifting the aggregates in water they were separated into the following aggregate classes > 2 mm; < 2 mm; 2-1 mm, and < 1 mm. The adoption time in the no-till system favored soil aggregation. The mean weighted diameter (MWD) of the soil aggregates and the percentage of aggregates greater than 2 mm increased with adoption time in the no-till system at the 0-5 cm depth. The NF and NT12 treatments had higher MWD values in the 0-5 cm layer. CT had the highest percentage of aggregates smaller than 1 mm.
Aggregation in a distroferric red nitosol under no-till, conventional tillage, and native forest systems
Keywords: adoption time; management systems; geometric mean diameter